PROSES KONSTRUKSI MAKNA DALAM BAHASA JAWA DAN INDONESIA - Deli Nirmala (LITERA, 2015)
AbstractThis study aims to describe meaning construction processes in Javanese and Indonesian.It employed cognitive linguistic theories. The data sources were written and spokenlanguages in newspapers, books on Javanese and Indonesian proverbs, and conversations.The data were collected through the documentation and reflective-instrospective methods.They were analyzed using the referential and abductive inferential methods. Based onthe results of the analysis, it can be concluded that meanings are constructed based onthe experiences embodied in a human’s mind through a conceptualization process. Thereare facts showing how meanings are constructed, for example, metaphors, proverbs,derivational forms, three language metafunctions, and a variety of language uses indifferent situations.Keywords: meaning, construction